FULFILLMENT OF THE RIGHTS TO RELIGIOUS EDUCATION OF MUSLIM WIVES BY HUSBAND NON-MOSLIM PERSPECTIVE OF INDONESIAN LEGAL PERSPECTIVE (Case Study in Panggeldlangu Village, Butuh District, Purworejo Regency) - Rizki Ana Rahma (State Institute of Islamic Studies (IAIN) Salatiga, 2022)
Marriage must be carried out by two people who believe in the same beliefs. The Islamic religion views that if in a marriage there is a husband or wife who changes religion, then the marriage becomes fasakh and is illegitimate to be maintained. But legally, marriages can only be broken up due to death, divorce and court decisions. A married couple who converted but did not apply for divorce in court is still considered a legal marriage. Therefore, the obligations and rights of husband and wife, one of whom has changed religions, must still be carried out considering that their marriage is still legally valid. One of the obligations described in the Compilation of Islamic Law Article 80 Paragraph 3 is that the husband is obliged to provide religious education to his wife. Therefore. This study aims to examine how the implementation of fulfilling the right of a Muslim wife to be given religious education by her non-Muslim husband from a positive law perspective. The type of research used is field research with a qualitative descriptive method and uses a juridical-empirical approach. As for data collection technique by way of interviews. Furthermore, emphasizing the results of observations and then drawing conclusions based on the results of observations in the form of data that has been collected in the form of words from interviews. The results of this study concluded that First, the implementation of fulfilling the rights of Muslim wives to receive Islamic religious education from non-Muslim husbands was not carried out This is because the fulfillment of the right to religious education by teaching prayers and teaching the knowledge of the Qur'an is not done by non-Muslim husbands. The representation of the fulfillment of the right to Islamic religious education granted by a non-Muslim husband is carried out only by giving permission to his wife to participate in the study of religious assemblies. Second, the analysis of the fulfillment of religious education regulated in the Compilation of Islamic Law Article 80 Paragraph 3 as the right of a wife from her husband is not appropriate, this is because the science of monotheism and the science of fiqh which should be taught is not taught by the husband because the husband is non-Muslim. Fulfillment of the right to religious education in accordance with Article 80 Paragraph 3 Compilation of Islamic Law is carried out by non-Muslim husbands, namely by giving permission to the wife to learn religious science from religious assemblies.